PELATIHAN KOMUNIKASI EFEKTIF ADMIN SHOPEE UNTUK MENINGKATKAN RATING DAN ULASAN KONSUMEN DI TOKO MEBEL DUA PUTRA - Aprilia, Ika Fitri; Sariani, Ni Luh (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The Shopee marketplace has become one of the strategic channels for increasing sales for businesses, including Mebel Dua Putra. However, the lack of knowledge among staff about how to build effective digital communication has resulted in a decline in consumer ratings and reviews on the Shopee platform. The objective of this community service project is to provide effective communication training to Shopee management staff at Mebel Dua Putra to improve customer interaction and enhance the store's reputation through the e-commerce platform. The implementation method consists of three stages: preparation, training, and implementation of results. The training materials include techniques for responding to messages persuasively, creating engaging caption copywriting, and post-purchase follow-up strategies. The results of this activity demonstrated an improved understanding of effective digital communication among staff, as well as an increased awareness of the importance of responding to customers in a friendly and solution-oriented manner. Evaluation was conducted through direct observation and discussions with management. With this training, it is hoped that Mebel Dua Putra can maintain customer loyalty through positive reviews and a strong digital reputation on Shopee.